2018
DOI: 10.1097/phm.0000000000000877
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Effectiveness of Ultrasound-Guided Corticosteroid Injection Above Versus Below the Median Nerve in Mild to Moderate Carpal Tunnel Syndrome

Abstract: Both above and under median nerve ultrasound-guided steroid injection techniques were effective in reducing the symptoms, improving the function, and improving electrodiagnostic and sonographic findings of carpal tunnel syndrome. However, the amount of improvement in the outcomes did not differ between groups, implying that none of technique has the superiority over another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…15 However, due to inconsistent results from published studies, controversy continues about the optimal strategy between short-and long-axis injection for CTS. 12,13,[16][17][18] In our clinical practice, both short-and long-axis injections were effective for HD in patients with CTS. Moreover, we observed that hydrodissecting both the FR and the SSCT seemed to enhance the therapeutic benefits of HD, based on patients' clinical presentations.…”
Section: Resultsmentioning
confidence: 89%
“…15 However, due to inconsistent results from published studies, controversy continues about the optimal strategy between short-and long-axis injection for CTS. 12,13,[16][17][18] In our clinical practice, both short-and long-axis injections were effective for HD in patients with CTS. Moreover, we observed that hydrodissecting both the FR and the SSCT seemed to enhance the therapeutic benefits of HD, based on patients' clinical presentations.…”
Section: Resultsmentioning
confidence: 89%
“…Among similar studies, Babaei-Ghazani et al, compared the clinical effectiveness of ultrasound-guided local triamcinolone injection “above” versus “below” the median nerve in CTS patients 23. They found that all outcome measures such as VAS, Boston questionnaire, EDX and US parameters improved significantly in both groups at 6 weeks, and these improvements were persevered up to 12-week follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies evaluate different US-guided techniques. Babaei-Ghazani et al 25 compared in-plane ulnar US-guided corticosteroid injection with "above" and "below" the median nerve approaches and concluded that both techniques were effective in symptom relief and functional improvement; as well they observed almost equal change in electrodiagnostic and sonographic parameters. In our study, we used in-plane radial versus the widely used ulnar approach for the carpal tunnel injection.…”
Section: Discussionmentioning
confidence: 99%